Anti-tumor effect and mechanistic study of elemene on pancreatic carcinoma - Jin Long; Zhe Liu; Lian Hui (BMC Complementary and Alternative Medicine, 2019)
Abstract Background Elemene is an effective anticancer component extracted from Zingiberaceae plants. This work was aimed to evaluate the anti-tumor effect and mechanism actions of elemene on pancreatic carcinoma in vitro and in vivo. Methods The anti-proliferation experiment was measured by Methylthiazolyldiphenyl-tetrazolium bromide (MTT) method in the time of 24, 48 and 72 h in three different dosages. The cell cycle was detected by flow cytometer after 12 h treatment. Forty-eight nude mice were subcutaneously xenograft with BxPC-3 pancreatic cancer cells and divided into four groups: Control group and high, medium, low dosage of elemene (20, 40 and 60 mg/kg) treatment groups. Immunoblot and immunohistochemical methods were applied to detect the protein expression of P53 and Bcl-2 in the tumor of pancreatic cancer xenografts. H & E staining was used to detect the histopathological changes in each group. Results A significant inhibition effect was observed in the anti-proliferation of BxPC-3 and Panc-1 cells in vitro in the time course of 24, 48 and 72 h with a dose dependent manner. The cell cycle results showed that elemene could arrest pancreatic cancer cells in the S phase after 12 h treatment in BxPC-3 and Panc-1 cell line. The in vivo BxPC-3 xenografts study exhibited that elemene was significantly decreased the tumor size in the high dosage group, compared to control group. And there is no any significant change in body weight of all animals. H&E pathology section result showed that treatment with elemene significantly decreased the inflammation cells and reduced the histopathological changes with a dose-dependent manner. Meanwhile, treatment with elemene significantly up-regulates the protein expression of P53, while down-regulate the protein expression of Bcl-2 in the tumor tissues, respectively. Furthermore, the western blot result showed that treatment with elemene increased the expression of P53 and decreased the expression of Bcl-2, compared with the control group, which is similar to the results of immunohistochemical staining. Conclusions This study suggests that elemene has a potential anti pancreatic cancer effect, down-regulation the protein expression of Bcl-2 and up-regulation the protein expression of P53 in a dose dependent manner may be is the anti-tumor mechanism.